Marriage Premium with Productivity Heterogeneity - Roberto Bonilla; Francis Kiraly; John Wildman (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using an equilibrium model of inter-linked frictional labour and marriage markets, we establish the existence of male marriage premium within a given productivity group, as well as a clear ranking of premia across different groups. We find supporting evidence using Chinese data.
Keywords: D83; J12; J16; J31; 330; constrained sequential search; marriage premium